SIREKAP sebagai Instrumen Democratization Technology: Analisis Yuridis Normatif terhadap Keandalan Sistem dan Potensi Sengketa Pemilu di Indonesia: SIREKAP as an Instrument of Democratization Technology: A Normative Legal Analysis of System Reliability and Potential for Election Disputes in Indonesia - Hikmah Putri Pristi Sari; Lio Bijumes (Universitas Muhammadiyah Palu, 2026)
The use of information technology in election administration is inevitable in modern democratic states. One such technological implementation is the Vote Recapitulation Information System (SIREKAP) introduced by the Indonesian General Elections Commission (KPU). Normatively, election technology should ensure legal certainty, data reliability, transparency, and the prevention of electoral disputes. Empirically, however, the implementation of SIREKAP in the 2024 General Election revealed various problems, including discrepancies between uploaded data and official C.Hasil Plano forms, technical system failures, and declining public trust in the vote recapitulation process. This study aims to analyze the legal standing and reliability of SIREKAP as a form of democratization technology and to examine the potential election disputes arising from its use. This research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that SIREKAP is legally positioned merely as a supporting tool regulated by KPU regulations and lacks a strong statutory basis. System unreliability and weak legal foundations increase the risk of both procedural and result-based election disputes. Therefore, strengthening the legal framework, conducting independent system audits, and establishing dispute mitigation mechanisms are necessary to ensure that election technology aligns with the principles of direct, general, free, secret, honest, and fair elections.